1994
DOI: 10.1002/j.1460-2075.1994.tb06249.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino acid-base contacts in the Myc-DNA complex by site-specific bromouracil mediated photocrosslinking.

Abstract: Myc binds to a 6 bp 2‐fold symmetric DNA site: 5′‐C‐3A‐2C‐1G+1T+2G+3‐3′. Using site‐specific 5‐bromouracil mediated photocrosslinking, we show that His336 of Myc contacts, or is close to, the thymine 5‐methyl group at 2‐fold symmetry‐related positions ‐2 and +2 of the DNA site in the Myc‐DNA complex. Our results strongly suggest that homologous amino acids of Myc and Max make equivalent contacts in the respective protein‐DNA complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Competitive gel shift analysis confirmed that sites lacking these groups were bound with lower affinity by Krox20 and NGFI-A VOL. 15,1995 DNA BINDING BY NGFI-A AND RELATED PROTEINS 2283…”
Section: Discussionmentioning
confidence: 99%
“…Competitive gel shift analysis confirmed that sites lacking these groups were bound with lower affinity by Krox20 and NGFI-A VOL. 15,1995 DNA BINDING BY NGFI-A AND RELATED PROTEINS 2283…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from fusion proteins consisting of GAL4 and c-Myc suggested that the c-Myc transactivation domain is localized to its first 143 amino acids (93). Immediately N terminal to the dimerization domain is a domain rich in basic amino acids which directly contacts specific DNA sequences within the DNA major groove (41,45,56,57,60,143,144,185). c-Myc DNA binding sites (both canonical [5Ј-CAC GTG-3Ј] and noncanonical) have been identified by using a variety of in vitro protein-DNA binding assays (26,27,144).…”
Section: C-myc Transcription Factor Its Binding Partner Max and Madmentioning
confidence: 99%
“…The photoactivated cross-linking reagent BrU, an isosteric analog of thymine, has been widely used to identify positions in a recognition site that are in close contact with a DNA-binding protein (2,4,8). The formation of a BrU-mediated covalently linked protein-DNA complex indicates that the protein is in van der Waals contact with the methyl group of a substituted thymine.…”
Section: Mutations Of Base Pairs Outside Of the Carg Box Effect Transmentioning
confidence: 99%
“…The cross-linking efficiency is ϳ4% at position 15 but falls to Ͻ1% at position 14. The higher efficiency of cross-linking found at position 15 may indicate the close proximity of an aromatic amino acid (His, Phe, Trp, or Tyr) (2,8,49).…”
Section: Mutations Of Base Pairs Outside Of the Carg Box Effect Transmentioning
confidence: 99%